Angiotensin II type 1 receptor and the activation of Myosin Light-Chain Kinase and Protein Kinase C-βII: Mini Review - Smith, Gerry A (Journal of Cardiology and Cardiovascular Medicine, 2020)
The involvement of the angiotensin II type 1 receptor in the Frank-Starling Law of the Heart, where the various activations are very limited, allows simple analysis of the kinase systems involved and thence extrapolation of the mechanism to that of angiotensin control of activation of cardiac and skeletal muscle contraction. The involvement of phosphorylation of the myosin light chain in the control of contraction is accepted but not fully understood. The involvement of troponin-I phosphorylation is also indicated but of unknown mechanism. There is no known signal for activation of myosin light chain kinase or Protein Kinase C-βII other than Ca2+/calmodulin but the former is constitutively active and thus has to be under control of a regulated inhibitor, the latter kinase may also be the same. Ca2+/calmodulin is not activated in Frank-Starling, i.e. there are no diastolic or systolic [Ca2+] changes. I suggest here that the regulated inhibition is by myosin light chain phosphatase and/or β-arrestin. Angiotensin activation, not involving G proteins. is by translocation of the β-arrestin from the sarcoplasm to the plasma membrane thus reducing its kinase inhibition action in the sarcoplasm. This reduced inhibition has been wrongly attributed to a mythical downstream agonist property of β-arrestin.